ARAH INOVASI PENDIDIKAN DI INDONESIA: SEBUAH TINJAUAN SISTEMATIK MENUJU PENDIDIKAN MAJU - Miftahul Jannah, Yunita; Lukman, Apriyaldi; Senoaji Wibowo, Muhammad; Putri, Annisa; Rifqoh, Fany (Institute Agama Islam Tafaqquh Fiddin Dumai, 2025)
Educational innovation has become an important topic in discussions about education development around the world, including in Indonesia. In an ever-changing social context, educational innovation is not only needed to improve the quality of learning, but also to ensure that education is accessible and relevant to all levels of society. This research method uses Systematic Literature Review (SLR) to review educational innovations in Indonesia. The process includes the determination of research questions, inclusion and exclusion criteria, literature search in the Scopus database, article filtering, and data analysis. The findings are synthesized to provide a comprehensive overview and recommendations for future educational development. Overall, these journals show that educational innovation in Indonesia is not only focusing on new learning methods, but also on policy development, teacher training, and the use of technology to create a better learning environment. By continuing to adopt and develop this innovation, it is hoped that the quality of education in Indonesia can improve significantly. The conclusion of this study shows that educational innovation in Indonesia faces various challenges, but also offers opportunities for improvement in the quality of education. Through the SLR approach, relevant patterns and trends were found, as well as recommendations for educational policies and practices, including related to current curriculum changes and also several collaborations with various circles as a reinforcement of Indonesia's higher education direction.